Pharmaceutical company payments to Japanese breast cancer practice guideline authors - Anju Murayama; Kenichi Higuchi; Keerthana R. Byreddy; Kugo Hinari; Yuki Senoo (Clinical and Translational Discovery, 2024)
Abstract Background The creation of breast cancer practice guidelines requires proper management of financial relationships with drug companies, as they can introduce conflicts of interest (COIs) among guideline authors. However, little is known about the specific landscape and fraction of financial interactions between the authors of the Japanese Breast Cancer Society Clinical Practice Guidelines for Breast Cancer, edition 2022 (JBCS2022) and drug companies. Methods Using payment data publicly disclosed by major drug companies in Japan, this study analysed the personal payments made to the authors of JBCS2022 between 2016 and 2020. We performed descriptive analyses on the payment data. Results Of the 149 JBCS2022 authors, 115 (77.2%) received at least one personal payment totaling $3 828 455 from drug companies between 2016 and 2020. The average and median payment amounts per author were $25 772 (standard deviation: $58 197) and $2761 (interquartile range: $322‒$15 828), respectively. The total annual payments per JBCS2022 authors between 2016 and 2019 increased from $588 054 in 2016 to $967 802 in 2019. The JBCS2022 chairperson and vice‐chairperson received $246 936 (fourth highest) and $216 744 (fifth highest) over the 5 years. More than 60% of personal payments to the JBCS2022 authors were not declared by the authors as they were below the declaration threshold set by the Japanese Breast Cancer Society. However, nine authors undeclared personal payments summing $594 615 even though these payments were higher than the thresholds. Conclusion This study demonstrated that the majority of the breast cancer guideline authors received personal payments from drug companies in Japan. Furthermore, the majority of payments were not declared because of the less transparent COI policy.